PEMBELAJARAN DISCOVERY TERBIMBING BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP FUNGSI EKSPONENSIAL DIKAJI DARI MOTIVASI BELAJAR - Pratiwi, Eka; Suratman, Dede; Noviani, Evi; Hamdani, Hamdani; Siregar, Nurfadilah (Universitas Bhinneka PGRI, 2026)
This study aims to analyze the effect of guided discovery learning assistes by the GeoGebra application on students’ conceptual understanding of exponential functions, examined from the perspective of learning motivation in grade XI at SMA Santo Paulus Pontianak. The study employed a quantitative method with a pre-experimental design of the one group pretest-posttets. The subjects of this study consisted of 56 eleventh-grade students who were grouped into high, medium, dan low learning categories.The instruments used were a conceptual understanding test, a learning motivation questionnaire, and an interview guidelines. The results showed that 9 students were categorized as having high motivation, 35 students as medium motivation, and 12 students as low motivation. The test data indicate in increase in conceptual understanding score of exponential functions by 47,62 for the high-motivation group, 48,85 for the medium-motivation group, and 21,23 for the low-motivation group. Furthermore, the test data were analyzed using the Wilcoxon test for the overall data as well as for the high- and medium-motivation groups, while the paired sample t-test was applied for the low-motivation group. The results indicated that guided discovery learning assisted by GeoGebra had a significant effect on students’ conceptual understanding of exponential functions, with effect sizes categorized as very strong across all levels of learning motivation.